(untitled) - Aggarwal, Vinod K. (New York, 2003)
Focusing on market strategies as well as nonmarket interactions between firms and governments, Aggarwal (political science, business, and public policy; U. of California at Berkeley) presents nine chapters American investment and trade strategies in Asian countries, with discussion of European and Asian strategies being left for companion volumes. Largely taking a case study approach, the contributors examine recent evolutions of entry strategy by American firms. Topics include the accounting industry in Japan, the chemical industry across Asia, telecommunications firms in Japan, and software and electronics in Japan. A final chapter assesses the relative values of the described market and nonmarket strategies
Keywords: Export marketing,Export marketing,Strategic planning,Strategic planning; Management,Management; United States,Asia,United States,Asia